Indonesian Historiography: From Nationalist Disentangling to Global Reconnection - Reid, Anthony (IKAT: The Indonesian Journal of Southeast Asian Studies, 2023)
This article originated in a keynote lecture to the 10th Indonesian National History Conference (KSNI) in 2016, the theme of which was Maritime History. The founders of those national conferences in the 1950s and ‘60s were seeking to disentangle Indonesia’s history and destiny from a Dutch-centric perspective, and create an Indonesia-centric history with its own vantage point and values. This article argues that they succeeded so well that Indonesian history is now dangerously detached from world history at a time when the new generation lives in a globalized world.  Indonesia’s pride in its own history can provide plenty of entry points into global history, whether economic, religious, intellectual or social.  History training must beware creating different histories for each nation-state lest it become the problem for international understanding, rather than the solution.